Implementation of a Practical Life Program to Improve the Independence of Group B Children - Priyantiningsih, P; Hastuti, Isnaini Budi (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
Purpose: This study aims to explore the influence of Practical Life activities on the development of independence in early childhood, specifically focusing on children aged 5–6 years at BA Aisyiyah Jetis III Sukoharjo. The research highlights how early independence can shape confident, intelligent, and self-reliant individuals ready to face future challenges. Methodology: This research employed a qualitative approach. Data were collected through observation, interviews, and documentation, and were analyzed using the Miles and Huberman model, which includes data reduction, data presentation, and verification. The implementation of the Practical Life program was examined in three stages: planning, execution during school routines, and assessment. Results: The findings indicate that Practical Life activities—rooted in the Montessori method—effectively support the development of children's independence. These activities, embedded in everyday routines such as self-care, organizing materials, and simple household tasks, help children internalize independent behaviors naturally. The consistent application of these activities during school hours contributed significantly to students' growing independence. Applications/Originality/Value: This study offers practical insights for early childhood educators and parents on how simple, daily routines can be powerful tools for fostering independence in children. It contributes to the growing body of literature supporting Montessori-based methods in PAUD (Early Childhood Education) institutions and provides a model that can be replicated in similar educational settings.